2018
DOI: 10.1093/cvr/cvy150
|View full text |Cite
|
Sign up to set email alerts
|

Decreased mitochondrial respiration in aneurysmal aortas of Fibulin-4 mutant mice is linked to PGC1A regulation

Abstract: AimThoracic aortic aneurysms are a life-threatening condition often diagnosed too late. To discover novel robust biomarkers, we aimed to better understand the molecular mechanisms underlying aneurysm formation.Methods and resultsIn Fibulin-4R/R mice, the extracellular matrix protein Fibulin-4 is 4-fold reduced, resulting in progressive ascending aneurysm formation and early death around 3 months of age. We performed proteomics and genomics studies on Fibulin-4R/R mouse aortas. Intriguingly, we observed alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 50 publications
4
38
0
Order By: Relevance
“…32 Decreased mitochondrial function and increased ROS are associated with the downregulation of PGC1A in Fibulin-4 mutant mice with aneurysmal aortas. 33 Melatonin attenuates the development of diabetes-induced cardiac dysfunction by preventing mitochondrial fission via the SIRT1-PGC1α pathway. 34 Our study showed that BP significantly increased the expression of PGC1α, while SIRT1 silencing reduced the PGC1α level and BP function, indicating that the effects of BP on mitochondria and oxidative stress might be mediated by SIRT1-mediated PGC1α regulation.…”
Section: Discussionmentioning
confidence: 99%
“…32 Decreased mitochondrial function and increased ROS are associated with the downregulation of PGC1A in Fibulin-4 mutant mice with aneurysmal aortas. 33 Melatonin attenuates the development of diabetes-induced cardiac dysfunction by preventing mitochondrial fission via the SIRT1-PGC1α pathway. 34 Our study showed that BP significantly increased the expression of PGC1α, while SIRT1 silencing reduced the PGC1α level and BP function, indicating that the effects of BP on mitochondria and oxidative stress might be mediated by SIRT1-mediated PGC1α regulation.…”
Section: Discussionmentioning
confidence: 99%
“… 7 van der Pluijm et al . 8 used proteomics, genomics, and functional experiments to study thoracic aortas of aneurysmal Fibulin-4R/R animals. Fibulin-4R/R mice showed alterations in protein composition affecting predominantly extracellular matrix (ECM) and cytoskeleton proteins, but also mitochondrial proteins and up-regulation of TGFβ1.…”
mentioning
confidence: 99%
“…Mitochondrial biogenesis and function are typically tightly coupled in the heart . To determine whether mitochondrial biogenesis was impaired in hyperglycemic cardiomyocytes and, therefore, contributed to mitochondrial disorder, we assessed the expression of PGC‐1 α, which plays a critical role in controlling mitochondrial biogenesis and function in the heart under physiological or pathological conditions . Associated with the morphological defects observed in mitochondria, the mRNA expression levels of PGC‐1α, nuclear respiratory factor 1 (NRF1), mitochondrial transcription factor A (TFAM), and other genes related to mitochondrial biogenesis decreased significantly in HG‐induced H9c2 cells (Figure F) and NRCM (Figure K).…”
Section: Resultsmentioning
confidence: 99%